2016
DOI: 10.1371/journal.pone.0150442
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Diurnal and Stress-Related Variability of Cadmium-Metallothionein Gene Expression in Land Snails

Abstract: The terrestrial Roman snail Helix pomatia has successfully adapted to strongly fluctuating conditions in its natural soil habitat. Part of the snail’s stress defense strategy is its ability to express Metallothioneins (MTs). These are multifunctional, cysteine-rich proteins that bind and inactivate transition metal ions (Cd2+, Zn2+, Cu+) with high affinity. In Helix pomatia a Cadmium (Cd)-selective, inducible Metallothionein Isoform (CdMT) is mainly involved in detoxification of this harmful metal. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Conversely, in kidneys, the cytoprotective antioxidant machinery involves the ROS scavenger function of MTs, leaving the MT genes responsive to oxidative stress injury. Considering that MTs are often used as a biomarker of cellular damage following environmental pollution [24,27,60,61], these findings also underlined the importance of focusing on the appropriate tissues during biomonitoring studies and knowing the effective content of constitutive MTs in the analyzed tissues to avoid collecting misleading reports.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in kidneys, the cytoprotective antioxidant machinery involves the ROS scavenger function of MTs, leaving the MT genes responsive to oxidative stress injury. Considering that MTs are often used as a biomarker of cellular damage following environmental pollution [24,27,60,61], these findings also underlined the importance of focusing on the appropriate tissues during biomonitoring studies and knowing the effective content of constitutive MTs in the analyzed tissues to avoid collecting misleading reports.…”
Section: Discussionmentioning
confidence: 99%
“…at night) (Zhang et al, 2009). Previous research has also found diurnal rhythmicity in phase II conjugating glutathione-S-transferases and phase III transporters, including ATP-binding cassette transporter (ABC transporters) and metallothionein, although daily patterns vary between protein families (Pedrini-Martha et al, 2016;Zhang et al, 2009). Phase II enzymes also include other transferases such as sulfotransferases and nonconjugation enzymes, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…These findings consistent with Dallinger et al(2004) who found that there is a strong correlation between heavy metals, particularly Cd accumulation, and MT concentration. As well, Pedrini-Martha et al (2016) reported that, MT genes can be up regulated in response to exposure to the corresponding metal ion. In addition, Roch et al (1982), Olsson and Haux (1986), Sulaiman et al (1991) and Hylland et al (1992) evidenced that an elevated level of MT in fish indicates that the fish has been exposed to heavy metals Pb,Cu and Cd.…”
Section: Discussionmentioning
confidence: 88%